PENGEMBANGAN PERMAINAN REDI DALAM PENINGKATAN EFIKASI DIRI BAGI SISWA SMA - Kristanti, Teofani Irene; Pravesti, Cindy Asli (Universitas Muria Kudus, 2021)
The purpose of this research is to develop REDI (Roda Efikasi Diri) game to increase the self-efficacy of students. This research and development method uses a Research and Development procedure, using steps: 1) preliminary study, 2) media development, and 3) media testing. Based on the material expert’s assessment, an average score of 0.81 was produced with a decent category. Based on the media expert’s assessment, an average score of 0.93 was obtained with a decent category. The result of the user test assessment is 96.67% in the very valid category. Based on the result of a limited field test, it was obtained tcount 1.172 ttable 0.727, so that H0 is rejected and Ha is accepted. So it can be concluded that REDI game is effective for increasing students self-efficacy.